In-Depth Opto-Electrical Analysis of Ni:Cds Film Towards the Performance as Ag/Ni:Cds/Fto Schottky Diode - Singh, D (Elsevier B.V., 2023)
Nickel doped cadmium sulfide (Ni:CdS) thin films are deposited onto glass and FTO substrate using spray pyrolysis technique. The effect of annealing temperature on the thin films and its morphological, microstructural, optical dispersion, linear-nonlinear and electrical, properties are extensively investigated by using various techniques such as field emission scanning electron microscope (FESEM) and atomic force microscopy (AFM), X-ray diffraction (XRD) and ultraviolet visible (UV-VIS) diffuse reflectance spectroscopy. Morphological studies revealed that doped thin films surface is almost homogeneous and well-covered. Peaks associated with Ni, Cd and S elements are present in EDS analysis, which confirm the composition of the films. The energy band calculation using the Tauc plot from the recorded absorption spectra reveals the decrement in the energy gap from 3.75 eV to 3.61 eV and the refractive index is in the range of 2.57–2.62. The effect of annealing temperature on complex dielectric constant are also analyzed. Moreover, the dispersion of refractive index is calculated in terms of Wemple-DiDomenico approach. Third order susceptibility and nonlinear refractive index are calculated of Ni:CdS films. The designed Ag/Ni:CdS/FTO Schottky diode is tested under illumination conditions, and the empirical diode parameters, viz. ideality factor, barrier height, series resistance etc. are influenced by annealing temperature. © 2023 Elsevier B.V.